2021
DOI: 10.1007/s00405-020-06563-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of olfactory and gustatory dysfunctions in COVID-19 patients in India

Abstract: Purpose The ongoing coronavirus disease 19 pandemic is spreading at an alarming rate across the globe. Sudden onset loss of smell and/or taste has been increasingly reported as a symptom of COVID-19. However, prevalence of these symptoms, and its severity varies widely between studies, with little data on its duration and recovery rate. Since this significantly impacts the quality of life of patients, there is a need for a study to provide insight into the loss of smell or taste in terms of its correlation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
13
1
1
Order By: Relevance
“…Another study done on 718 patients reported that 101 (14%) patients experienced either altered smell or taste, with 52 (7%) experiencing both altered smell and taste. Seventy-seven (10.7%) patients had altered smell and 76 patients had altered taste sensation (10.5%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study done on 718 patients reported that 101 (14%) patients experienced either altered smell or taste, with 52 (7%) experiencing both altered smell and taste. Seventy-seven (10.7%) patients had altered smell and 76 patients had altered taste sensation (10.5%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Jerome R. Lechien et al showed 79.5% of patients recovered normal smell sense within 2 months following the onset of loss of smell [ 31 ]. Pradipt ranjan sahoo et al reported that 92% patients regained olfaction and 96% regained taste sensation, on follow-up at the 2 weeks of the PCR positivity [ 24 ]. The varied time taken for the recovery in different patients may be due to the various pathophysiological mechanisms causing damage to neuronal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilinska et al, concluded that Caucasians might have excessive ACE2 variants expressed on the sustentacular cells of their olfactory cleft, hence resulting in the binding of the SARS-CoV-2 virus with higher affinity, resulting in higher frequency olfactory symptoms as compared to the East Asians, who have lesser ACE2 variants [45]. Also, a metanalysis done by Bartheld et al signifies that ethnicity is a pivotal factor in contributing to the difference observed in incidence of chemosensory dysfunction amongst East Asian and Caucasian population as quoted by the study done by Pradip Ranjan [46].…”
mentioning
confidence: 99%
“…La pérdida de olfato es la alteración más frecuente, con una prevalencia del 77% cuando se evalúa mediante mediciones objetivas[57]. Estas disfunciones afectan principalmente a pacientes jóvenes, tienen un predominio femenino y son más prevalentes en casos leves a moderados[56,58].En la mayoría de los casos la recuperación de ambas disfunciones se produce durante el primer o segundo mes, generalmente de forma completa[59][60][61][62]. No obstante, los datos de diferentes estudios publicados muestran un tiempo de persistencia bastante variable: 17-56% a las 4 semanas, 10-23% a las 8 semanas, y 4-46% a las 12 semanas[63] y por tanto podrían considerarse parte del síndrome post-COVID.…”
unclassified